한국형 우울장애 약물치료 알고리듬 2025 (IV): 여성 및 노인 - 왕성민(Sheng-Min Wang), 정영은(Young-Eun Jung), 박원명(Won-Myong Bahk), 서정석(Jeong Seok Seo), 김낙영(Nak-Young Kim), 최원석(Won-Seok Choi), 우영섭(Young Sup Woo), 박성용(Sung-Yong Park), 김원(Won Kim), 이정구(Jung Goo Lee), 양찬모(Chan-Mo Yang), 성형모(Hyung Mo Sung), 정종현(Jong-Hyun Jeong), 이상열(Sang-Yeol Lee), 윤보현(Bo-Hyun Yoon), 김문두(Moon-Doo Kim), 민경준(Kyung Joon Min) (Singyŏng chŏngsin ŭihak, 2025)
Objectives Depressive disorders vary widely by age and sex, necessitating individualized treatment approaches. Women experience hormonal fluctuations across their lifespan, contributing to distinctive symptom patterns, while older adults often present with atypical features such as cognitive decline or somatic complaints. With the rising prevalence of depression in Korea, the Korean Medication Algorithm Project for Depressive Disorder (KMAP-DD) has been periodically revised to offer practical, consensus-based treatment guidMethods KMAP-DD 2025 involved a nationwide expert survey of 136 psychiatrists, and 97 responses were received (71.3% response rate). The questionnaire was based on previous editions and modified to reflect recent clinical developments. A 9-point modified RAND scale was used to rate the appropriateness of each treatment. Recommendations were categorized into first-, second-, or third-line options based on confidence interval thresholds and chi-square analyses. Results First-line treatments for premenstrual dysphoric disorder included selective serotonin reuptake inhibitors and desvenlafaxine. During pregnancy, antidepressant monotherapy and repetitive transcranial magnetic stimulation (rTMS) were recommended for non-psychotic depression, while antidepressant–antipsychotic combinations and electroconvulsive therapy were favored for psychotic cases. Postpartum depression strategies depended on symptom severity and psychotic features. In older adults, antidepressant monotherapy remained the first-line treatment for mild-to-moderate episodes; combination with antipsychotics was preferred in psychotic depression. Escitalopram was consistently the top-rated antidepressant across groups. Conclusion KMAP-DD 2025 maintains core treatment recommendations while incorporating emerging interventions such as rTMS. These updated guidelines underscore the importance of personalized and safe treatment strategies for depression in women and older adults.elines tailored to local clinical settings. KCI Citation Count: 0